Sleep inertia during a simulated 6-h on/6-h off fixed split duty schedule. (2nd July 2016) - Hilditch, Cassie J.; Short, Michelle; Van Dongen, Hans P. A.; Centofanti, Stephanie A.; Dorrian, Jillian; Kohler, Mark; Banks, Siobhan
ABSTRACT: Sleep inertia is a safety concern for shift workers returning to work soon after waking up. Split duty schedules offer an alternative to longer shift periods, but introduce additional wake-ups and may therefore increase risk of sleep inertia. This study investigated sleep inertia across a split duty schedule. Sixteen participants (age range 21–36 years; 10 females) participated in a 9-day laboratory study with two baseline nights (10 h time in bed, [TIB]), four 24-h periods of a 6-h on/6-h off split duty schedule (5-h TIB in off period; 10-h TIB per 24 h) and two recovery nights. Two complementary rosters were evaluated, with the timing of sleep and wake alternating between the two rosters (2 am/2 pm wake-up roster versus 8 am/8 pm wake-up roster). At 2, 17, 32 and 47 min after scheduled awakening, participants completed an 8-min inertia test bout, which included a 3-min psychomotor vigilance test (PVT-B), a 3-min Digit-Symbol Substitution Task (DSST), the Karolinska Sleepiness Scale (KSS), and the Samn–Perelli Fatigue Scale (SP-Fatigue). Further testing occurred every 2 h during scheduled wakefulness. Performance was consistently degraded and subjective sleepiness/fatigue was consistently increased during the inertia testing period as compared to other testing times. Morning wake-ups (2 am and 8 am) were associated with higher levels of sleep inertia than later wake-ups (2 pm and 8 pm). These results suggest that split duty workers should recognise the potential for sleep inertia after waking, especially during the morning hours.